Leadership Styles Affecting Organizational Citizenship Behaviour in Selected IT Organizations in Chennai - Angeline, S.; Sudha, S. (Prabandhan: Indian Journal of Management, 2015)
Leadership style is the manner and approach of providing direction, implementing plans, and motivating people. It is the ability that affects the performance of individuals in organizations. This study aims to identify the leadership styles practiced in selected IT organizations and its effect on the employee's organizational citizenship behaviour (OCB). The leadership styles considered for the study were transactional and transformational leadership styles. The research was carried out by administering a well-structured questionnaire and the responses were collected. It was found that the leaders in the selected IT organizations exhibited a combination of transactional and transformational leadership styles. The various qualities were also discussed in the study to decide the leader's style. The study also brought out that the impact of transactional and transformational leadership styles on OCB will lead to the benefit of the organization by increasing productivity, efficiency, and satisfaction among the employees.